Alert citizenry as an antidote to war - Giacomo Corneo (Freie Universität Berlin, School of Business & Economics, 2023)
What can be done to reduce the likelihood of future wars? While states' decisions that bear on war are ultimately made by their political leaders, strengthening ordinary citizens' control of those leaders is vital to reduce the risk of future wars. This thesis can be broken down into two claims: first, there is a war bias of political leaders; second, people's control over those leaders may successfully counteract that bias. Claim nê1 has that in some situations political leaders and citizens have substantially divergent interests with respect to policies that risk the outbreak of war. Political leaders may have a war bias that is so strong that they prefer war occurring with high probability whereas citizens prefer peace occurring with high probability. Claim nê2 has that in some situations strengthening citizens' control of political decision-makers may be decisive to prevent a war. As I'll argue shortly, this empowerment can be beneficial only if sufficiently many citizens have previously become alert by productively engaging in a distinctive cognitive effort. This requirement points to a precise responsibility of intellectuals.
urn:nbn:de:kobv:188-refubium-41896-5
Keywords: 320; political leader; people`s control; war; peace; war prevention; peace agreement